Investigation on factors that contribute to the abandonment of building in construction industry in Malaysia - Nur Farhayu, Ariffin; Mohd Faizal, Md Jaafar; Mohamad Idris, Ali; Noram Irwan, Ramli; Khairunisa, Muthusamy (EDP Sciences, 2018)
In Malaysia, the construction sector is one of the important sectors that contribute to economic growth and employments. However, a major concern facing the construction industry is the growing rate of delays in project delivery. In the worse cases, the projects were abandoned due to some reasons when the contract period ended. Abandoned building defines as construction work that has been continuously stalled for 6 months or more, during the project completion period or beyond the scheduled date of completion. When the projects become abandoned, it gives an adverse effect on many parties such as the developer, contractor, consultant and also client. According to previous researchers, the abandonment of building causes a serious problem and need some mitigation plan to avoid this problem from occurring. This study will investigate the fundamental factors that contribute to the abandonment of building and projects in Malaysia based on the current data of the abandoned building in most states in Malaysia. The data was collected from the respondents who is in the construction industry and had experience working with abandoned housing project. Form the respondents perspective, it shows that the main factor contribute to the building abandonment is due to the financial problem facing by the developer company.